Automatic detection of technique during on snow XC-skiing - Bortolan, L.; Pellegrini, B.; Impellizzeri, F.; Schena, F. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Cross-country skiers are allowed to freely and dynamically choose the technique according to track slope and ambient condition. The recording of the technique adopted by the athlete on field is usually performed by filming the subject. This method provides a lot of Information but requires that the athlete is always in the field of view of the camera (Andersson E., 2010). The aim of the study was to describe the technique distribution automatically identified using a new methodology based on the pole force acquisition System.